The investigation on electrochemical denatured layer of 304 stainless steel. Issue 15 (18th November 2018) - He, Qianxi; Jin, Zhuji; Jiang, Guannan; Shi, Yuan
ABSTRACT: Electrochemical grinding (ECG) is one of nontraditional manufacturing methods that are widely used on various chromium alloys like 304 stainless steel and GCr15, etc. It has been considered that a thin passive film is formed on alloys during the electrochemical process and much research has been done on it. However, it is found that a kind of denatured layer (which is much thicker than passive film) is formed on 304 stainless steel surface during the process while the characteristics and influence factors of the denatured layer have been rarely focused. In this paper, an experimental study as well as a computational method were implemented to investigate characteristics of denatured layer on 304 stainless steel and influential mechanisms of electrochemical parameters on thickness of denatured layer. We found that the hardness of denatured layer was decreased by 70%, and third-order equations for predicting layer thickness under different electrochemical parameters were proposed. The obviously reduced hardness and controllable thickness of the denatured layer are expected to be of great significance in machining of chromium alloy.